Ab initio investigation of the first hydration shell of glucose. (October 2020) - Song, Ran; Chen, Dong; Suo, Chengxiang; Guo, Zhiheng
Abstract: The interaction between sugars and water molecules plays a crucial role in exploring the complex metabolic reactions of living systems. The fully random conformational search is employed to investigate the first hydration shell structure of glucose. The circumference of glucose is divided into three hydrate sites according to the location of water molecules. Especially, four water molecules can saturate hydrate site AI and while more water molecules will be required to saturate hydrate sites AIII and AII . Moreover, the hydration energies of water molecules at different hydration region indicate that the competition of the three hydrate sites for water molecules changes dynamically with the increase of water molecules. In addition, we calculate the Raman spectra of the hydrated glucose, which are in good agreement with the experimental and theoretical Raman spectra of the glucose solution. Graphical abstract: Image 1 Highlights: The first hydration shell of glucose is successfully achieved. The first hydration shell of glucose fully describes the interaction between glucose and surrounding waters at the microscopic level. As the number of water molecules increases, the competition of the three hydrate sites changes dynamically. The first hydration shell of glucose under the CPCM model can simulate the Raman vibration of the glucose solution efficiently.